KEBIJAKAN PERLINDUNGAN HUKUM BAGI PEKERJA RUMAH TANGGA MELALUI KEPASTIAN HUKUM (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
AbstractThis study examines the legal protection of Domestic Workers (PRT) in Indonesia through the aspect of legal certainty. The results of the study show that legal protection for domestic workers is still very weak, due to the absence of specific regulations that explicitly regulate their status, rights, and obligations. Existing regulations, such as the Manpower Law, have not directly accommodated the needs of domestic workers because the RUU on Protection of Domestic Workers which has long been initiated has not been ratified. This condition creates an uncertain legal position for domestic workers and is vulnerable to various forms of rights violations, exploitation, and violence. International comparisons show that Indonesia is still lagging behind in building a fair and inclusive protection system for domestic workers. Therefore, strategic steps are needed to formulate comprehensive regulations and provide legal certainty in order to effectively protect the basic rights of domestic workers. This study is expected to contribute ideas for the renewal of fairer and more sustainable legal policies for domestic workers in Indonesia.